Safety, tolerability, and immunogenicity of a single dose 4-antigen or 3-antigen Staphylococcus aureus vaccine in healthy older adults: Results of a randomised trial. Issue 2 (5th January 2017) - Creech, C. Buddy; Frenck, Robert W.; Sheldon, Eric A.; Seiden, David J.; Kankam, Martin K.; Zito, Edward T.; Girgenti, Douglas; Severs, Joseph M.; Immermann, Frederick W.; McNeil, Lisa K.; Cooper, David; Jansen, Kathrin U.; et al.
Highlights: SA4Ag is a novel multi-antigen vaccine that targets S. aureus virulence factors. A single dose of SA4Ag was well-tolerated in healthy adults aged 65–85 years. A robust functional immune response was elicited to each vaccine component. Antibody rise was rapid and sustained after one dose of SA4Ag vaccine. SA4Ag is a promising candidate vaccine to prevent invasive S. aureus infections. Abstract: Background: The decline in immune function with age is a challenge to vaccine development. Following an initial study in adults aged 18–64 years, this study evaluated the safety and immunogenicity of Staphylococcus aureus ( S. aureus ) 4-antigen (SA4Ag) and 3-antigen (SA3Ag) vaccine in older adults. SA3Ag included capsular polysaccharide serotypes 5 and 8 (CP5 and CP8) conjugated to the nontoxic mutant form of diphtheria toxin (CRM197 ) and a recombinant version of clumping factor A (ClfA). SA4Ag included these antigens, with the addition of a recombinant manganese transporter C (rP305A or MntC). Both vaccines were unadjuvanted. Methods: In this double-blind, sponsor-unblinded, placebo-controlled, phase 1/2 study, 284 healthy adults (aged 65–85 years) were randomised to receive a single dose of one of three formulations of SA4Ag with escalating dose levels of rP305A, SA3Ag, or placebo. Functional immune responses were measured using opsonophagocytic activity (OPA) killing and fibrinogen-binding inhibition (FBI) assays; immunogenicity was also assessed using a competitive Luminex® immunoassay (cLIA). T-cell responses were measured in a small subgroup of subjects using intracellular cytokine staining (ICS) assays. Results: The results demonstrated rapid and robust functional immune responses to all antigens in healthy older adults. A high proportion of active vaccine recipients met the pre-defined antibody thresholds for each antigen at Day 29. SA4Ag elicited a dose-level response to rP305A with up to a 13-fold rise in cLIA titres at Day 29. Opsonophagocytic activity (OPA) assays showed >50- and >20-fold rises in functional titres using S. aureus strains expressing CP5 and CP8, respectively, at Day 29. T-cell cytokine responses were not substantially above background levels. There were no safety concerns in this study population and no increases in adverse events with higher rP305A dose levels. Conclusions: Single-dose vaccination of SA4Ag and SA3Ag in healthy adults aged 65–85 years safely induced rapid and robust functional immune responses, supporting further development of SA4Ag for the prevention of S. aureus disease in adults up to age 85 years. Trial registration number: NCT01643941 .